Authoritative Parenting and School Support As Predictors Of Preschoolers’ Social Efficacy - Sulistyorini Sulistyorini; Ahmad Samawi; Sri Wahyuni (Aulad: Journal on Early Childhood, 2025)
Social efficacy in early childhood plays a crucial role in developing successful social relationships and emotional growth; however, it often does not develop optimally. This study aims to analyze the influence of authoritative parenting and school social support on children’s social efficacy in kindergartens throughout Diwek District, Jombang Regency. The study employed a quantitative approach with an ex post facto design. The sample consisted of 328 parents selected using the cluster proportional random sampling technique. The research instruments were validated through Pearson validity tests and Cronbach’s Alpha reliability tests (α = 0.974). Data were analyzed using SPSS version 26 through t-tests, F-tests, and multiple linear regression analyses. The findings revealed that authoritative parenting and school social support had a significant effect on children’s social efficacy. These results emphasize the importance of collaboration between families and schools in fostering social efficacy among early childhood learners.